An X-ray diffraction and X-ray absorption spectroscopy joint study of neuroglobin - Arcovito, Alessandro; Moschetti, Tommaso; D’Angelo, Paola; Mancini, Giordano; Vallone, Beatrice; Brunori, Maurizio; Della Longa, Stefano (Archives of biochemistry and biophysics, 2008)
Neuroglobin (Ngb) is a member of the globin family expressed in the vertebrate brain, involved in neuroprotection. A combined approach of X-ray diffraction (XRD) on single crystal and X-ray absorption spectroscopy (XAS) in solution, allows to determine the oxidation state and the structure of the Fe–heme both in the bis-histidine and the CO-bound (NgbCO) states. The overall data demonstrate that under X-ray the iron is photoreduced fairly rapidly, and that the previously reported X-ray structure of ferric Ngb [B. Vallone, K. Nienhaus, M. Brunori, G.U. Nienhaus, Proteins 56 (2004) 85–92] very likely refers to a photoreduced species indistinguishable from the dithionite reduced protein. Results from the XAS analysis of NgbCO in solution are in good agreement with XRD data on the crystal. However prolonged X-ray exposure at 15 K determines CO release. This preliminary result paves the way to experiments aimed at the characterization of pentacoordinate ferrous Ngb, the only species competent in binding external ligands such as O 2, CO or NO.